Requirements needed for Using Computer in Teaching at Higher Education, In Sudan, from the Point of View of Educational Specialists - Sadek, Hatem Abdel Majid (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the necessary requirements needed for Using Computer in Teaching at Higher Education from the Point of View of Educational Specialists, The researcher used the analytical descriptive method , the size of the sample in which the study was applied was (50) from the teaching staff, The researcher has used questionnaire as a study tool, The most important findings of the study are: The study has come to the fact that the majority of the researchers managed to answer the study areas, which are summarized in (the requirements needed for Using, Computer in teaching at Higher Education, The most important recommendations of the study are: Providing all the requirements needed to put into practice, (for the teaching staff members, the student teacher, in the syllabus and the physical educational environment which was determine by the study employ Computer in teaching in the institutions of the higher education in Sudan.